The interplay of technology, family, and identity: Chinese adolescents’ self-presentation on Douyin - Zhang, Qimin (Frontiers in Psychology, 2025)
In the context of digitization and globalization, social media platforms, particularly TikTok, have become central spaces for adolescents’ self-presentation and social interactions. While TikTok has gained global popularity, its Chinese counterpart, Douyin, serves a similar role but within a distinct regulatory and cultural framework. This study investigated how Chinese adolescents constructed their digital identities on Douyin and examined the role of parents in this process. By integrating Erving Goffman’s self-presentation theory and Albert Bandura’s social learning theory, the research considered perspectives from adolescents and their parents across diverse socioeconomic backgrounds in Shanxi Province, China. Through in-depth qualitative interviews, it captured individuals’ psychological experiences and behavioral patterns. Thematic analysis revealed that adolescents’ digital behaviors are driven by psychological demands such as belonging, self-identity, and social recognition. The findings demonstrated a complex interplay between adolescents’ “front-stage” performances and “back-stage” behaviors on Douyin. Furthermore, parenting styles—whether restrictive or directive—significantly influenced adolescents’ behavioral and psychological adaptation. Adolescents developed multifaceted perceptions of their identities through observation, imitation, and content creation, affected by both the global digital landscape and local cultures. Parental mediation either fostered adolescents’ psychological security or undermined their autonomy when overly restrictive. Overall, this study uncovers the psychological complexities of adolescents’ digital identity construction and emphasizes the interplay among family, culture, and technology. By extending Goffman’s and Bandura’s theories to the Chinese cultural context, it offers valuable insights into adolescents’ psychological development and digital engagement.